Hubungan Bobot Isi dan Kemantapan Agregat Tanah dengan Biomassa Tanaman Jagung Manis dan Cabai Merah setelah diberikan Kombinasi Terak Baja dan Bokashi Sekam Padi pada Andisol, Lembang - Henly Yulina; Rina Devnita; Rachmat Heryanto (Agrikultura, 2019)
ABSTRACTRelationship between bulk density and soil agaregate stability on biomass of sweet corn and red chili after given combination steel slag and bokashi of husk on Andisol LembangThe objective of this research was to find out relationship between bulk density and soil agaregate stability on biomass of sweet corn and red chili after given combination steel slag and bokashi of husk on Andisol Lembang.This study used a Randomized Block Design Factorial with two factors. The first factor was steel slag and the second factor was bokashi of husk. Each of them consisted of 4 levels of 0%, 2.5%, 5.0% and 7.5% with two replications. The result of this research showed there was relationship between bulk density and soil agaregate stability on biomass of sweet corn and red chili, however only the biomass of red chili was influenced of bulk density and soil agaregate stability.Keywords: Steel slag, Bokashi of husk, Bulk density, Soil agaregate stability, Plant biomassABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan antara bobot isi dan kemantapan agregattanah terhadap biomassa tanaman jagung manis dan cabai merah setelah diberikan kombinasi terakbaja dengan bokashi sekam padi pada Andisol Lembang. Penelitian menggunakan Rancangan AcakKelompok Pola Faktorial dengan dua faktor. Faktor pertama terak baja dan faktor kedua bokashisekam padi masing-masing 4 taraf yaitu 0%, 2,5%, 5,0%, dan 7,5%, diulang dua kali. Hasil penelitian menunjukkan bahwa terdapat hubungan antara bobot isi dan kemantapan agreagat tanahdengan biomassa tanaman jagung manis dan cabai merah, namun hanya biomassa tanaman cabaimerah yang dipengaruhi oleh bobot isi dan kemantapan agregat tanah.Kata Kunci: Terak baja, Bokashi sekam padi, Bobot isi, Kemantapan agregat, Biomassa tanaman